Hubungan Self-Efficacy dengan Academic Burnout saat Pandemi COVID-19 pada Mahasiswa Keperawatan Universitas Tanjungpura Pontianak - Zehro Masitoh; Triyana Harlia Putri; Faisal Kholid Fahdi (Malahayati Nursing Journal, 2022)
ABSTRACT The COVID-19 pandemic has had various negative impacts in the world of education, including the change in learning methods from offline to fully online. These conditions can increase academic burnout in students which affects the lecture process. There are individual factors that influence academic burnout, one of which is self-efficacy or student self-confidence. Knowing the relationship between self-efficacy and academic burnout during the COVID-19 pandemic for Nursing students at Tanjungpura University, Pontianak. This research is quantitative in nature using a correlation design with a cross sectional approach. The research instrument used the GSES and MBI-SS questionnaires on 185 mahasiswats who were taken by purposive sampling technique with stratified random sampling. Bivariate test in this study using Spearman rho. The results of the correlation test show that there is a relationship between self-efficacy and academic burnout during the COVID-19 pandemic for Nursing students at Tanjungpura University Pontianak with a value (p-value = 0.019) and a value (r = -0.172). The results of the research are negative, which means that the higher the self-efficacy, the lower the academic burnout and vice versa. There is a relationship between self-efficacy and academic burnout during the COVID-19 pandemic for Nursing students at Tanjungpura University, Pontianak. Keywords: Self-efficacy, Academic Burnout, COVID-19 Pandemic  ABSTRAK Kondisi pandemi COVID-19 memberikan berbagai dampak negatif dalam dunia pendidikan, diantaranya perubahan metode pembelajaran dari luring menjadi sepenuhnya daring. Kondisi tersebut dapat meningkatkan kejenuhan akademik (academic burnout) pada mahasiswa yang berpengaruh terhadap proses perkuliahan.Terdapat faktor individu yang mempengaruhi academic burnout, salah satunya adalah self-efficacy atau keyakinan diri mahasiswa. Mengetahui hubungan antara self-efficacy dengan academic burnout saat pandemi COVID-19 pada mahasiswa Keperawatan Universitas Tanjungpura Pontianak. Penelitian bersifat kuantitatif menggunakan desain korelasi dengan pendekatan cross sectional. Instrumen penelitian mengggunakan kuesioner GSES dan MBI-SS pada 185 mahasiswa yang diambil dengan teknik purposive sampling dengan stratified random sampling. Uji bivariate dalam penelitian ini menggunakan Spearman rho. Hasil uji korelasi menunjukkan bahwa terdapat hubungan antara self-efficacy dengan academic burnout saat pandemi COVID-19 pada mahasiswa Keperawatan Universitas Tanjungpura Pontianak dengan nilai (p-value=0,019) dan nilai (r=-0,172). Hasil penelitian berarah negatif, yang bermakna semakin tinggi self-efficacy maka semakin rendah academic burnout dan sebaliknya. Terdapat hubungan antara self-efficacy dengan academic burnout saat pandemi COVID-19 pada mahasiswa Keperawatan Universitas Tanjungpura Pontianak. Kata Kunci :Self-efficacy, Academic burnout, Pandemi COVID-19